1997
DOI: 10.1177/095624789700900111
|View full text |Cite
|
Sign up to set email alerts
|

Low-income rental housing: are South African cities different?

Abstract: A significant proportion of the black urban population in South Africa rent accommodation. Surveys conducted in two low-income settlements in Cape Town and Johannesburg show that the rental housing scene is in many ways similar to that found in other Third World cities. Landlords are older than their tenants, many are female, their families are larger, their homes have more space and better services. Few landlords make any money and landlord-tenant relationships are not generally conflictive. At the same time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…This had the effect of encouraging informal urban tenancy, in rooms within existing houses (Crankshaw & Parnell 1996 ; Lemanski 2011 ), in shared hostel accommodation (Ramphele 1993 ) and later in backyard shacks which proliferated with the rescinding of apartheid legislation from the late 1980s onwards (Gilbert et al . 1997 ; Lemanski 2009 ).…”
Section: Backyard Dwellersmentioning
confidence: 99%
See 2 more Smart Citations
“…This had the effect of encouraging informal urban tenancy, in rooms within existing houses (Crankshaw & Parnell 1996 ; Lemanski 2011 ), in shared hostel accommodation (Ramphele 1993 ) and later in backyard shacks which proliferated with the rescinding of apartheid legislation from the late 1980s onwards (Gilbert et al . 1997 ; Lemanski 2009 ).…”
Section: Backyard Dwellersmentioning
confidence: 99%
“…It has been estimated, for example, that in Africa and Asia informal rental provides over half the housing needs of the population in urban areas, and a third of those in Latin America (Gilbert et al . 1997 ). However, a comparative study conducted in Brazil and South Africa revealed that whilst informal rental has been a livelihood strategy in Brazil for some time, it was only regularly employed to supplement household income by poor South African households more recently (Gilbert et al 1997 ) and even today is generally a subsistence strategy for the landlord rather than a profit-making endeavour (Shapurjee & Charlton 2013 ).…”
Section: Backyard Dwellersmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of affordable rental housing is a crisis for many urban areas the world over, especially so in cities with constrained housing markets. The global south is particularly affected (Gilbert et al 1997;Watson & McCarthy 1998;Collinson 2011;Baranoff 2016). Part of the problem is that, since the 1970s, state provision of affordable housing has declined due to lack of capacity.…”
Section: Introductionmentioning
confidence: 99%
“…For the low-income segment, social housing is a type of rental housing managed by the government or private sectors (Oxley et al, 2011). In Global South, private rental housing by petty landlords plays a pivotal role in affordable housing for the low-income (Gilbert et al, 1997;Parnell, 1991) segment and provides additional income to petty landlords ( UN-Habitat, 2011).…”
Section: Introductionmentioning
confidence: 99%